Early and late endocrine complications of COVID-19. Issue 9 (20th September 2021) - Kazakou, Paraskevi; Paschou, Stavroula A; Psaltopoulou, Theodora; Gavriatopoulou, Maria; Korompoki, Eleni; Stefanaki, Katerina; Kanouta, Fotini; Kassi, Georgia N; Dimopoulos, Meletios-Athanasios; Mitrakou, Asimina
Abstract : Endocrine system plays a vital role in controlling human homeostasis. Understanding the possible effects of COVID-19 on endocrine glands is crucial to prevent and manage endocrine disorders before and during hospitalization in COVID-19-infected patients as well as to follow them up properly upon recovery. Many endocrine glands such as pancreas, hypothalamus and pituitary, thyroid, adrenal glands, testes, and ovaries have been found to express angiotensin-converting enzyme 2 receptors, the main binding site of the virus. Since the pandemic outbreak, various publications focus on the aggravation of preexisting endocrine diseases by COVID-19 infection or the adverse prognosis of the disease in endocrine patients. However, data on endocrine disorders both during the phase of the infection (early complications) and upon recovery (late complications) are scarce. The aim of this review is to identify and discuss early and late endocrine complications of COVID-19. The majority of the available data refer to glucose dysregulation and its reciprocal effect on COVID-19 infection with the main interest focusing on the presentation of new onset of diabetes mellitus. Thyroid dysfunction with low triiodothyronine, low thyroid stimulating hormone, or subacute thyroiditis has been reported. Adrenal dysregulation and impaired spermatogenesis in affected men have been also reported. Complications of other endocrine glands are still not clear. Considering the recent onset of COVID-19 infection, the available follow-up data are limited, and therefore, long-term studies are required to evaluate certain effects of COVID-19 on the endocrine glands.